2022
DOI: 10.1002/jhet.4484
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and fungicidal activities of novel ethylenediamine bridged thiazole derivatives containing oxime ether or oxime ester moieties

Abstract: To study the influence of changing the piperidine ring on the fungicidal activity, at the same time based on the successful experience of opening the oxazoline ring, a series of novel ethylenediamine bridged thiazole derivatives containing oxime ether and oxime ester moieties were designed, synthesized, and first evaluated for their fungicidal activities against phytophthora capsaicae in vitro. The bioassays results showed that the target compounds possessed moderate fungicidal activities against phytophtho‐ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The activities of oxime ester compounds were lower than oxime ether compounds when the two nitrogen atoms are positioned on the opposite sides. Subsequently, based on the aforementioned results, a series of novel oxathiapiprolin derivatives containing oxime ether and oxime ester moieties were synthesized, in which the piperidine ring was opened ( Tian et al, 2022 ) ( Figure 3B ). Their antifungicidal activities were evaluated and showed that the target compounds possessed moderate fungicidal activities against Phytophthora capsici , and the activities of these compounds were lower than that of oxathiapiprolin, suggesting that the piperidine ring was crucial for the fungicidal activities of these compounds.…”
Section: Structural Modification Of Commercial Oxathiapiprolinmentioning
confidence: 99%
“…The activities of oxime ester compounds were lower than oxime ether compounds when the two nitrogen atoms are positioned on the opposite sides. Subsequently, based on the aforementioned results, a series of novel oxathiapiprolin derivatives containing oxime ether and oxime ester moieties were synthesized, in which the piperidine ring was opened ( Tian et al, 2022 ) ( Figure 3B ). Their antifungicidal activities were evaluated and showed that the target compounds possessed moderate fungicidal activities against Phytophthora capsici , and the activities of these compounds were lower than that of oxathiapiprolin, suggesting that the piperidine ring was crucial for the fungicidal activities of these compounds.…”
Section: Structural Modification Of Commercial Oxathiapiprolinmentioning
confidence: 99%
“…cubensis, and P. infestans in vivo however, its activity decreased after further opening of the piperidine ring (compound 11 ) . Replacing the pyrazole group was a feasible and efficient strategy for modifying the structure of the X-ray-coated plasmid of OXA.…”
Section: Introductionmentioning
confidence: 99%